Separator for secondary battery, manufacturing method thereof, and secondary battery including the same

JP2025505748APending Publication Date: 2025-02-28LG ENERGY SOLUTION LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2024547698
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2022-11-01
Filing Date
2023-10-31
Publication Date
2025-02-28

AI Technical Summary

Benefits of technology

【0033】 本発明の一側面によれば、バインダースラリーのコーティング容易性を向上させ得るとともに、セルの抵抗を減少させる分離膜を提供できる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025505748000001_ABST
    Figure 2025505748000001_ABST
Patent Text Reader

Abstract

There is provided a separator for a secondary battery that simultaneously achieves uniform coating of a binder slurry and reduced cell resistance, which are in a trade-off relationship. An embodiment of the present invention provides a separator for a secondary battery, comprising a porous substrate, a preliminary separator including a coating layer disposed on one side of the porous substrate, a first binder layer disposed on one side of the coating layer, and a second binder layer disposed on the other side of the porous substrate, wherein the first binder layer and the second binder layer each include the same or different surfactants, and satisfy the following formula 1: [Formula 1] ΔP(s / 100cc)=|Ps-Pc|<120 In the formula 1, Ps is the air permeability of the separator for a secondary battery, and Pc is the air permeability of the preliminary separator.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention claims the benefit of the filing date of Korean Patent Application No. 10-2022-0143298, filed with the Korean Intellectual Property Office on November 1, 2022, the entire contents of which are incorporated herein by reference.

[0002] The present invention relates to a separator for a secondary battery, and more particularly to a separator for a secondary battery, a manufacturing method thereof, and a secondary battery including the same. [Background technology]

[0003] Lithium-ion batteries, a representative example of secondary batteries, are basically composed of a positive electrode, a separator, a negative electrode, and an electrolyte. They are representative energy devices with high energy density that can be charged and discharged while reversibly converting chemical energy and electrical energy, and are widely used in small electronic devices such as mobile phones and notebooks. Recently, their application to hybrid electric vehicles (HEVs), plug-in electric vehicles (Plug-in EVs), electric bicycles (E-bikes), and energy storage systems (ESSs) has been rapidly expanded in response to environmental issues, high crude oil prices, energy efficiency, and storage. Lithium-ion batteries are stable electrochemical elements insulated by a separator, but since a short circuit between the positive and negative electrodes can occur due to internal or external battery abnormalities or impacts, which can cause heat generation and explosion, ensuring the thermal and chemical safety of the separator as an insulator is the most important thing to consider.

[0004] Meanwhile, in order to improve the energy density of secondary batteries, there is a demand for thinner separators. Although insulating properties and thermal stability can be improved by coating a porous substrate with a coating layer containing inorganic particles, the current situation is that there is a lack of technology to uniformly coat inorganic particles of 100 nm or more to less than 1.5 μm. Summary of the Invention [Problem to be solved by the invention]

[0005] An object of the present invention is to provide a separator for a secondary battery which simultaneously achieves uniform coating properties of a binder slurry and reduced cell resistance, which are in a trade-off relationship.

[0006] Another object of the present invention is to provide a separator for a secondary battery that has a high adhesive strength to an electrode during the manufacture of an electrode assembly by heat and pressure, and can effectively prevent defects such as separator breakage.

[0007] It is yet another object of the present invention to provide a separator for a secondary battery, which can increase the energy density of a secondary battery by uniformly coating a binder slurry on one side of a porous substrate or a coating layer to reduce the thickness of the separator.

[0008] It is yet another object of the present invention to provide a method for manufacturing the separator for a secondary battery, which has improved coating properties of a binder slurry.

[0009] It is yet another object of the present invention to provide a secondary battery including the separator for secondary batteries.

[0010] The objects of the present invention are not limited to the objects mentioned above, and other objects and advantages of the present invention not mentioned can be understood from the following description and will be more clearly understood from the embodiments of the present invention. In addition, it will be easily understood that the objects and advantages of the present invention can be realized by the means and combinations thereof described in the claims. [Means for solving the problem]

[0011] In order to achieve the above object, according to a first aspect of the present invention, there is provided a separator for a secondary battery, comprising: a porous substrate; and a coating layer disposed on one side of the porous substrate; a first binder layer disposed on one side of the coating layer; and a second binder layer disposed on the other side of the porous substrate, wherein the first binder layer and the second binder layer each contain the same or different surfactants, and satisfy the following formula 1:

[0012] [Formula 1]

[0013] ΔP(s / 100cc)=|Ps-Pc|<120

[0014] In the formula 1, Ps is the air permeability of the separator for a secondary battery, and Pc is the air permeability of the preliminary separator.

[0015] According to a second aspect of the present invention, the first binder layer and the second binder layer in the first aspect may each include a particulate binder that is the same as or different from each other. Here, the particulate binder may be defined as a binder that is not dissolved in a solvent contained in the binder layer forming composition. For example, the solubility of the particulate binder may be 1 g / 100 mL or less, 0.1 g / 100 mL or less, 0.01 g / 100 mL or less, or 0.001 g / 100 mL or less, more preferably 0 g / 100 mL, in the solvent of the binder layer forming composition.

[0016] According to a third aspect of the present invention, the particulate binder in the second aspect can include a first particulate binder and a second particulate binder different from the first particulate binder.

[0017] According to a fourth aspect of the present invention, in any one of the first to third aspects, the first and second particulate binders may each independently comprise one compound, two or more copolymers, or a mixture of two or more selected from the group consisting of polyacrylate (PA), polyacrylic acid (PAA), poly(vinylidene fluoride; PVDF), polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-HFP), poly(butyl acrylate; PBA), polystyrene (PS), poly(methyl methacrylate; PMMA), poly(ethylene oxide; PEO), and poly(siloxane).

[0018] According to a fifth aspect of the present invention, in any one of the second to fourth aspects, the surfactant may be independently included in an amount of more than 0 and less than 5.0 parts by weight relative to 100 parts by weight of the particulate binder.

[0019] According to a sixth aspect of the present invention, in any one of the first to fifth aspects, the surfactant may include a nonionic surfactant.

[0020] According to a seventh aspect of the present invention, in the sixth aspect, the nonionic surfactant can include one or more selected from the group consisting of perfluoroalkyltriethylene oxide methyl ethers, polyoxyethylene alkyl ethers, polyoxyethylene fatty acid esters, polyoxyethylene alkylphenol ethers, sorbitan fatty acid esters, polyoxyethylene sorbitan fatty acid esters, sucrose fatty acid esters, polyfluorobutane sulfonates, and polyethylene oxide-polypropylene oxide copolymers, each of which has an alkyl group with 6 carbon atoms.

[0021] According to an eighth aspect of the present invention, in any one of the first to seventh aspects, the coating layer may have a thickness of 0.1 to 10 μm.

[0022] According to a ninth aspect of the present invention, in any one of the first to eighth aspects, the first and second binder layers may each independently have a thickness of 0.05 to 10 μm.

[0023] According to a tenth aspect of the present invention, there is provided a method for manufacturing a separator for a secondary battery according to any one of the first to ninth aspects, comprising: coating one side of the coating layer with a first binder slurry, followed by drying to form the first binder layer; and coating another side of the porous substrate with a second binder slurry, followed by drying to form the second binder layer.

[0024] According to an eleventh aspect of the present invention, in the tenth aspect, the following formula 2 can be satisfied.

[0025] [Formula 2]

[0026] C A <50°

[0027] In the above formula 2, C Ais the contact angle of the first binder slurry with one surface of the coating layer at 25°C.

[0028] According to a twelfth aspect of the present invention, in the tenth or eleventh aspect, the following formula 3 can be satisfied:

[0029] [Formula 3]

[0030] C B <50°

[0031] In the above formula 3, C B is the contact angle of the second binder slurry with the other surface of the porous substrate at 25°C.

[0032] According to a thirteenth aspect of the present invention, there is provided a secondary battery including: a negative electrode; a positive electrode; a separator for a secondary battery according to any one of the first to ninth aspects interposed between the negative electrode and the positive electrode; and an electrolyte. Effect of the Invention

[0033] According to one aspect of the present invention, it is possible to provide a separator that can improve the ease of coating a binder slurry and reduce the resistance of a cell.

[0034] In accordance with another aspect of the present invention, the binder slurry is uniformly coated on one side of a porous substrate or a coating layer, thereby reducing the thickness of a separator and increasing the energy density of a secondary battery.

[0035] According to yet another aspect of the present invention, when manufacturing an electrode assembly using heat and pressure, the adhesive strength to the electrodes is increased, so that defects such as breakage of the separator can be effectively prevented.

[0036] In addition to the above-mentioned effects, specific effects of the present invention will be described below while explaining specific contents for carrying out the invention. [Brief description of the drawings]

[0037] [Figure 1] 1 is a vertical cross-sectional view of a separator for a secondary battery according to one embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0038] Hereinafter, each component of the present invention will be described in more detail so that a person having ordinary skill in the art to which the present invention pertains can easily implement the present invention. However, this is merely an example, and the scope of the present invention is not limited to the following content.

[0039] In this specification, the range of values ​​expressed using the term "~" refers to a range of values ​​including the values ​​described before and after the term as the lower and upper limits, respectively. When the upper and lower limits of any numerical range are disclosed in a plurality of values, the range of values ​​disclosed in this specification can be understood as any numerical range having any one value among the plurality of lower limits and any one value among the plurality of upper limits as the lower and upper limits, respectively. For example, when the specification states a~b or c~d, it can be understood that a or more and b or less, a or more and d or less, c or more and d or less, or c or more and b or less are described.

[0040] In this specification, the term "layer" or film may include a case where the layer or film is formed over the entire area when the area is observed, as well as a case where the layer or film is formed only over a part of the area. For example, the surface of the layer or film may be defined as including a flat form, a non-flat form, and a combination thereof, or a continuous form, a non-continuous form, and a combination thereof. For example, when another member is formed of a layer or film directly on one member, the coverage of the other member on the surface of the one member may be defined as 1% or more, 5% or more, 10% or more, 20% or more, 30% or more, 40% or more, 50% or more, 60% or more, 70% or more, 80% or more, 85% or more, 90% or more, 95% or more, or 99% or more.

[0041] In this specification, the average particle size of particles is the particle size D at which the cumulative percentage reaches 50% on a volume-based particle size distribution curve when measured by a laser diffraction particle size distribution analyzer. 50 It can be defined as:

[0042] In the present specification, the weight average molecular weight is a standard polystyrene-equivalent molecular weight, and can be analyzed using a GPC (gel permeation chromatography) device. Here, the GPC analysis method can use tetrahydrofuran as a developing solvent, and can be performed under the following analytical conditions: sample concentration 5 mg / mL, sample introduction amount 100 μL, temperature 40° C., and flow rate 1 mL / min.

[0043] In one aspect of the present invention, there is provided a separator for a secondary battery, comprising: a porous substrate; a coating layer disposed on one side of the porous substrate; a first binder layer disposed on one side of the coating layer; and a second binder layer disposed on the other side of the porous substrate, wherein the first binder layer and the second binder layer each contain the same or different surfactants, and the following formula 1 is satisfied:

[0044] [Formula 1]

[0045] ΔP(s / 100cc)=|Ps-Pc|<120

[0046] In the formula 1, Ps is the air permeability of the separator for a secondary battery, and Pc is the air permeability of the preliminary separator.

[0047] Conventionally, when the binder slurry is coated on the surface of a preliminary separator, the surface energy of the porous substrate and the coating layer are different, and the wetting of both surfaces is different. Therefore, when the binder slurry is coated on the surface of the preliminary separator, it is difficult to coat it uniformly. When a surfactant is added to the binder slurry to adjust the wettability, the ease of coating can be improved to a certain extent, but there is a problem that the surfactant blocks the pores of the preliminary separator or deforms the shape of the binder in the coating layer, increasing the air permeability and increasing the cell resistance. Therefore, the uniform coating property of the binder slurry and the cell resistance are in a trade-off relationship in which if one performance is high, the other performance is low, and it is difficult to achieve both performances.

[0048] According to one aspect of the present invention, by satisfying ΔP(s / 100cc)=|Ps-Pc|<120 and including a surfactant in the binder layer, the ease of coating of the binder slurry can be improved and a new parameter for reducing the resistance of the cell can be presented. If ΔP(s / 100cc)=|Ps-Pc|<120 is not satisfied, even if the binder layer includes a surfactant and the binder slurry has excellent coatability, the resistance of the cell including the separator can be excessively increased. If ΔP(s / 100cc)=|Ps-Pc|<120 is satisfied but the binder layer does not include a surfactant, the coatability of the binder slurry can be reduced and the number of uncoated spots can be excessively increased.

[0049] In accordance with another aspect of the present invention, a binder slurry including an optimal content of a surfactant is uniformly coated on one side of a porous substrate or a coating layer, thereby reducing the thickness of a separator and increasing the energy density of a secondary battery. In addition, during the manufacture of an electrode assembly using heat and pressure, the separator has high adhesion to the electrode, effectively preventing defects such as breakage.

[0050] The configuration of the present invention will be described in more detail below with reference to FIG.

[0051] 1.Separation membrane for secondary batteries

[0052] FIG. 1 is a vertical cross-sectional view of a separator for a secondary battery according to one embodiment of the present invention.

[0053] As shown in FIG. 1, a separator 100 for a secondary battery according to the present invention includes a preliminary separator 15, a first binder layer 30a, and a second binder layer 30b.

[0054] Spare separation membrane

[0055] The preliminary separation membrane 15 according to the present invention includes a porous substrate 10 and a coating layer 20. Specifically, the preliminary separation membrane 15 includes the porous substrate 10 and the coating layer 20 formed on only one surface of the porous substrate 10, and corresponds to a cross-section of a ceramic-coated separator (CCS).

[0056] (Porous base material)

[0057] The porous substrate 10 according to the present invention can provide a path for lithium ion migration while electrically insulating the negative electrode and the positive electrode to prevent short circuits, and can be a porous structure having high resistance to an electrolyte and fine pores.

[0058] The material of the porous substrate 10 may be any organic or inorganic material having electrical insulation properties, without any particular limitation. The porous substrate 10 may include at least one selected from the group consisting of polyolefin, polyethylene terephthalate, polybutylene terephthalate, polyacetal, polyamide, polycarbonate, polyimide, polyether ether ketone, polyether sulfone, polyphenylene oxide, polyphenylene sulfide, and polyethylene naphthalate, and may specifically include polyolefin. Polyolefin has excellent coating properties, and can reduce the thickness of the separator, thereby increasing the proportion of the electrode active material layer in the battery and increasing the capacity per volume. Specifically, the weight average molecular weight (M w ) may be 100,000 to 500,000 g / mol. If the weight average molecular weight of the polyolefin is less than the above range, it may be difficult to ensure sufficient mechanical properties, and if it exceeds the above range, the shutdown function may not be realized or molding may be difficult. The shutdown function refers to the function of blocking the movement of ions and preventing thermal runaway of the battery by dissolving the thermoplastic resin and closing the pores of the porous substrate when the temperature of the secondary battery increases.

[0059] In some examples, the thickness of the porous substrate 10 may be 3 to 50 μm or 4 to 15 μm. If the thickness of the porous substrate is less than the numerical range, the conductive barrier function may be insufficient, and if the thickness exceeds the numerical range, the resistance of the separator may be excessively increased.

[0060] In some examples, the average diameter of the pores in the porous substrate 10 is not particularly limited and may be specifically 10 to 100 nm. The pores in the porous substrate 10 are interconnected to each other, so that gas or liquid can pass from one side of the porous substrate to the other side.

[0061] (Coating layer)

[0062] The coating layer 20 according to the present invention can improve the mechanical strength and heat resistance of the separator for the secondary battery, and can increase the ion conductivity in the secondary battery.

[0063] The coating layer 20 according to the present invention is disposed on one side of the porous substrate 10. Specifically, since the coating layer 20 is disposed only on one side of the porous substrate 10, the amount of electrode active material can be increased by the reduced thickness compared to both sides, which may be advantageous for the energy density of the battery.

[0064] In some embodiments of the present invention, the packing density of the coating layer 20 is 0.1 to 20 g / cm 3 Specifically, it can be 0.5 to 12 g / cm 3 , more specifically, 1 to 3 g / cm 3 When the packing density of the coating layer is within the numerical range, the permeability of lithium ions may be favorable and the heat resistance of the separator may be maintained at an appropriate level. Meanwhile, the packing density is determined based on the unit area (m 2 ) is the density of the coating layer loaded to a height of 1 μm.

[0065] In some embodiments of the present invention, the thickness of the coating layer 20 may be 0.1 to 10 μm, specifically 1 to 3 μm, and more specifically 1.4 to 1.6 μm. When the thickness of the coating layer is within the above range, the insulating property and thermal stability of the separator can be improved, and the energy density of the battery can be improved.

[0066] The coating layer 20 according to the present invention may include a binder polymer and inorganic particles.

[0067] The binder polymer according to the present invention can link inorganic particles together and stably fix them. In some examples, the binder polymer can be polyvinylidene fluoride-co-hexafluoropropylene, polyvinylidene fluoride-co-trichloroethylene, polymethylmethacrylate, polyacrylonitrile, polyvinylpyrrolidone, polyvinylacetate, ethylene-vinyl acetate copolymer, polyethylene oxide, cellulose acetate, cellulose acetate butyrate, or cellulose acetate propionate. One or a mixture of two or more selected from the group consisting of acrylonitrile-styrene butadiene copolymer, polyimide, and styrene-butadiene rubber can be used.

[0068] According to another embodiment of the present invention, the weight ratio of the inorganic particles to the binder polymer (inorganic particles:binder polymer) may be 50:50 to 99:1, specifically 70:30 to 95:5. If the content ratio of the inorganic particles to the binder polymer is less than the above range, the content of the binder polymer may be high, which may reduce the function of improving the thermal stability of the separator, and the pore size and porosity may be reduced due to the reduction in the vacant space formed between the inorganic particles, which may cause a decrease in the performance of the final battery. If the content ratio exceeds the above range, the content of the binder polymer may be too low, which may weaken the peel resistance of the coating layer.

[0069] The inorganic particles according to the present invention can contribute to improving the mechanical strength and heat resistance of a separator for a secondary battery. Specifically, the inorganic particles are not particularly limited as long as they are electrochemically stable. That is, the inorganic particles that can be used in the present invention can be used in the range of operating voltages (e.g., Li / Li + There are no particular limitations as long as the oxidation and / or reduction reaction does not occur at a voltage of 0 to 5 V relative to the reference potential.

[0070] For example, when inorganic particles having a high dielectric constant are used as the inorganic particles, the inorganic particles can contribute to increasing the dissociation degree of the electrolyte salt, for example, the lithium salt, in the liquid electrolyte, thereby improving the ionic conductivity of the electrolyte. For the above reasons, the inorganic particles may be inorganic particles having a dielectric constant of 5 or more, inorganic particles having a lithium ion transfer ability, or a mixture thereof.

[0071] The inorganic particles having a dielectric constant of 5 or more are Al2O3, SiO2, ZrO2, AlO(OH), Al(OH)3, Mg(OH)2, BaSO4, TiO2, BaTiO3, Pb(Zr x Ti 1-x )O3(PZT, where 0 <x<1)、Pb 1-x La x Zr 1-y Ti y O3(PLZT, where 0 <x<1、0<y<1である)、(1-x)Pb(Mg 1 / 3 Nb2 / 3 )O 3-x It can be one or a mixture of two or more selected from the group consisting of PbTiO3 (PMN-PT, where 0 < x < 1), HfO2, SrTiO3, SnO2, CeO2, MgO, NiO, CaO, ZnO, and SiC.

[0072] The inorganic particles having the lithium ion transfer ability are lithium phosphate (Li3PO4), lithium titanium phosphate (Li x Ti y (PO4)3, 0 < x < 2, 0 < y < 3), lithium aluminum titanium phosphate (Li x Al y Ti z (PO4)3, 0 < x < 2, 0 < y < 1, 0 < z < 3), (LiAlTiP) x O y -based glass (0 < x < 4, 0 < y < 13), lithium lanthanum titanate (Li x La y TiO3, 0 < x < 2, 0 < y < 3), lithium germanium thiophosphate (Li x Ge y P z S w , 0 < x < 4, 0 < y < 1, 0 < z < 1, 0 < w < 5), lithium nitride (Li x N y , 0 < x < 4, 0 < y < 2), SiS2-based glass (Li x Si y S z , 0 < x < 3, 0 < y < 2, 0 < z < 4), and P2S5-based glass (Li x P y S z , 0 < x < 3, 0 < y < 3, 0 < z < 7) and can be one or a mixture of two or more selected from the group.

[0073] For example, the average particle size D 50 of the inorganic particles can be 1 nm to 10 μm for forming a coating layer with a uniform thickness and an appropriate porosity, specifically, it can be 10 nm to 2 μm, and more specifically, it can be 50 nm to 1 μm. The "average particle size D50 " means the particle size at the 50% point of the cumulative particle number distribution according to particle size. The average particle size can be measured using a laser diffraction method. Specifically, the powder to be measured is dispersed in a dispersion medium, and then the dispersion medium is introduced into a commercially available laser diffraction particle size measuring device (e.g., Microtrac S3500). When the particles pass through a laser beam, the difference in diffraction pattern according to particle size is measured, and the particle size distribution can be calculated.

[0074] First Binder Layer

[0075] According to one aspect of the present invention, the first binder layer 30a can improve the adhesive strength of the separator to the electrode when manufacturing an electrode assembly in which the separator and the electrode are stacked by applying heat and pressure, thereby improving ease of assembly of the electrode assembly and preventing defects such as folding of the separator.

[0076] The first binder layer 30a according to the present invention is disposed on one surface of the coating layer 20. Specifically, the thickness of the first binder layer 30a may be 0.01 to 100 μm, specifically 0.05 to 20 μm, more specifically 0.05 to 10 μm, further specifically 0.2 to 1 μm, and even more specifically 0.4 to 0.6 μm. When the thickness of the first binder layer 30a is within the above numerical range, the adhesive strength of the separator to the electrode is improved to improve the ease of assembling the electrode assembly, and the reduction in the energy density of the battery due to the separator being too thick can be prevented.

[0077] The first binder layer 30a according to the present invention contributes to the adhesive force of the separator to the electrode and may include a particulate binder dispersed in the binder slurry. By including the particulate binder in the first binder layer, the mobility of ions can be ensured through the spaces between the particulate binders, and the coatability and adhesive force can be adjusted by adjusting the particle size.

[0078] For example, the particulate binder may include one compound selected from the group consisting of polyacrylate (PA), polyacrylic acid (PAA), poly(vinylidene fluoride; PVDF), polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-HFP), poly(butyl acrylate; PBA), poly(styrene; PS), poly(methyl methacrylate; PMMA), poly(ethylene oxide; PEO), and poly(siloxane), and a copolymer of two or more of these compounds, or a mixture of two or more of these compounds.

[0079] In some embodiments, the average particle size D of the particulate binder 50 The thickness can be 30 to 3,000 nm, specifically, 50 to 1,000 nm, and more specifically, 100 to 800 nm.

[0080] According to yet another embodiment of the present invention, the particulate binder may include a first particulate binder and a second particulate binder that is the same as or different from the first particulate binder. The first and second particulate binders may each independently be one of the exemplary compounds for the particulate binder described above. When the particulate binder is composed of two or more types of binders, it is possible to effectively prevent the occurrence of defective appearance in the cell during the manufacturing process of the battery assembly, and to further improve the adhesive strength of the separator to the electrode.

[0081] The first binder layer 30a according to the present invention contains a surfactant to adjust the wetting of the first binder slurry that forms the first binder layer.

[0082] The surfactant according to the present invention may include a nonionic surfactant. Generally, surfactants are classified into anionic surfactants, cationic surfactants, amphoteric surfactants, and nonionic surfactants. Since secondary batteries are operated by electrochemical reactions due to the movement of lithium ions, nonionic surfactants may be preferred. For example, the nonionic surfactant may be one or two selected from the group consisting of fluorine-based compounds, silicon-based compounds, and substituted or unsubstituted hydrocarbon-based compounds, and specifically, may be one or two selected from the group consisting of perfluoroalkyltriethyleneoxide methyl ether, polyoxyethylene alkyl ether, polyoxyethylene fatty acid ester, polyoxyethylene alkylphenol ether, sorbitan fatty acid ester, polyoxyethylene sorbitan fatty acid ester, sucrose fatty acid ester, polyfluorobutane sulfonate, and polyethylene oxide-polypropylene oxide copolymer, each of which has 6 carbon atoms in the alkyl group.

[0083] The content of the surfactant according to the present invention may be more than 0 and less than 5.0 parts by weight based on 100 parts by weight of the particulate binder, specifically, 0.01 to less than 5.0 parts by weight, more specifically, 0.05 to less than 4.0 parts by weight, more specifically, 0.1 to 2.0 parts by weight, more specifically, 1.0 to 2.0 parts by weight, more specifically, 1.2 to 1.8 parts by weight, more specifically, 1.3 to 1.6 parts by weight, and more specifically, 1.4 to 1.6 parts by weight. According to one aspect, when the content of the surfactant satisfies the above numerical range, the first binder slurry is uniformly coated on one side of the coating layer, thereby reducing the thickness of the separator and increasing the energy density of the secondary battery, and at the same time, when the electrode assembly is manufactured by heat and pressure, the adhesive force to the electrode is increased, and thus a defect phenomenon such as the separator being broken can be effectively prevented. In another aspect, when the surfactant content is within the above range, the surfactant does not block the pores of the separator, thereby effectively preventing the battery resistance from becoming too high.

[0084] Second Binder Layer

[0085] Like the first binder layer 30a, the second binder layer 30b according to the present invention can improve the adhesive strength of the separator to the electrode when an electrode assembly in which a separator and an electrode are stacked is manufactured by applying heat and pressure, thereby improving ease of assembly of the electrode assembly and preventing defects such as folding of the separator.

[0086] The first binder layer 30a and the second binder layer 30b according to the present invention may each contain the same or different particulate binders.

[0087] The first and second binder layers 30a and 30b each contain the same or different surfactants. The content of the surfactant contained in the second binder layer 30b according to the present invention may be the same or different from the content of the surfactant contained in the first binder layer 30a. That is, the surfactants may each be independently contained in an amount of more than 0 and less than 5.0 parts by weight based on 100 parts by weight of the particulate binder.

[0088] The thickness of the second binder layer 30b may be the same as or different from the thickness of the first binder layer 30a, specifically, the same. That is, the thicknesses of the first and second binder layers may be independently 0.01 to 100 μm, specifically 0.05 to 20 μm, more specifically 0.05 to 10 μm, and even more specifically 0.2 to 1 μm. For example, the thickness of the first binder layer is 0.2 to 0.8 μm, and the thickness of the second binder layer is , can be 0.7 to 1.3 μm.

[0089] The separator for a secondary battery according to the present invention satisfies the following formula 1.

[0090] [Formula 1]

[0091] ΔP(s / 100cc)=|Ps-Pc|<120

[0092] In the formula 1, Ps is the air permeability of the separator for a secondary battery, and Pc is the air permeability of the preliminary separator. According to one aspect of the present invention, when the absolute value of the difference between the air permeability of the separator for a secondary battery and the air permeability of the preliminary separator is less than 120, the resistance of the cell including the separator may be low. When the absolute value of the difference between the air permeability of the separator for a secondary battery and the air permeability of the preliminary separator is 120 or more, the resistance of the cell including the separator may be excessively increased. When measuring the air permeability of the separator for a secondary battery and the air permeability of the preliminary separator, for example, an air permeability measuring device commonly used in the art (e.g., Asahi Seiko Co., Ltd. EG01-55-1MR model) can be used. Specifically, a measurement sample is fixed to the upper and lower tips of a hollow shape of the air permeability measuring device, and the time required for 100 cc of air to pass through the set pressure difference applied to the upper and lower tips can be measured.

[0093] According to one aspect of the present invention, by satisfying ΔP(s / 100cc)=|Ps-Pc|<120 and including a surfactant in the binder layer, the ease of coating of the binder slurry can be improved and a new parameter for reducing the resistance of the cell can be provided. If ΔP(s / 100cc)=|Ps-Pc|<120 is not satisfied, the resistance of the cell having the separator may increase excessively even if the binder layer includes a surfactant and the binder slurry has excellent coatability. If ΔP(s / 100cc)=|Ps-Pc|<120 is satisfied but the binder layer does not include a surfactant, the binder slurry has poor coatability and the number of uncoated spots may increase excessively. In another aspect of the present invention, a binder slurry containing an optimal amount of a surfactant is uniformly coated on one side of a porous substrate or a coating layer, thereby reducing the thickness of a separator and increasing the energy density of a secondary battery. In addition, during the manufacture of an electrode assembly using heat and pressure, the adhesive strength to the electrode is increased, effectively preventing defects such as separator breakage.

[0094] 2. Manufacturing method of separator for secondary battery

[0095] In yet another embodiment of the present invention, there is provided a method for manufacturing the separator for a secondary battery. The repeated descriptions of the above will be briefly described or omitted.

[0096] The method for manufacturing a separator for a secondary battery according to the present invention may include the steps of: coating one side of the coating layer with a first binder slurry, followed by drying to form the first binder layer; and coating another side of the porous substrate with a second binder slurry, followed by drying to form the second binder layer.

[0097] The method for coating the first binder slurry on one side of the coating layer or the method for coating the second binder slurry on the other side of the porous substrate are not particularly limited, and various coating methods in the art may be used. For example, the first and second binder slurries may be coated by gravure coating or slot die coating.

[0098] The drying time and drying temperature of the first and second binder slurries may be, for example, 5 minutes to 180 minutes and 15 to 75° C., respectively. However, in terms of actual process, it may be preferable that the drying time and drying temperature of the first and second binder slurries are the same.

[0099] The method for producing a separator for a secondary battery according to an embodiment of the present invention may satisfy the following formula 2.

[0100] [Formula 2]

[0101] C A <50°

[0102] In the above formula 2, C Ais the contact angle of the first binder slurry to one surface of the coating layer at 25° C. In the formula 2, the contact angle C of the first binder slurry to one surface of the coating layer is A When the contact angle C of the first binder slurry to one surface of the coating layer is less than 50°, the first binder layer can be coated with a uniform thickness without any uncoated area. A If the angle is more than 50°, uncoated spots of 1 mm or more may occur.

[0103] The method for manufacturing a secondary battery according to another embodiment of the present invention may satisfy the following formula 3.

[0104] [Formula 3]

[0105] C B <50°

[0106] In the above formula 3, C B is the contact angle of the second binder slurry to the other surface of the porous substrate at 25° C. In the formula 3, the contact angle C of the second binder slurry to the other surface of the porous substrate B When the contact angle C of the second binder slurry to the other surface of the porous substrate is less than 50°, the second binder layer can be coated with a uniform thickness without leaving any uncoated areas. B If the angle is more than 50°, uncoated spots of 1 mm or more may occur.

[0107] The contact angles of the first and second binder slurries may be measured at room temperature using a contact angle measuring device commonly used in the art (eg, Attension Theta Flex from Biolin Scientific).

[0108] 3.Secondary battery

[0109] According to another embodiment of the present invention, a secondary battery may be provided, the secondary battery separator interposed between the negative electrode and the positive electrode, and an electrolyte. The above-mentioned repeated descriptions will be briefly described or omitted.

[0110] According to yet another embodiment of the present invention, the first binder layer may be in contact with one of the negative electrode and the positive electrode, and the second binder layer may be in contact with the other of the negative electrode and the positive electrode. By having the first binder layer and the second binder layer in contact with the electrodes, adhesion of the separator to the electrodes is improved, and a battery assembly manufacturing process may be facilitated.

[0111] negative electrode

[0112] The negative electrode according to the present invention may include a negative electrode current collector and a negative electrode active material layer disposed on at least one surface of the negative electrode current collector. The negative electrode active material layer may include a negative electrode active material, a conductive material, and a negative electrode binder.

[0113] The negative electrode current collector can act as a passageway for transferring electrons from the outside so that an electrochemical reaction occurs in the negative electrode active material, or receiving electrons from the negative electrode active material and sending them to the outside. For example, the negative electrode current collector can be made of copper, stainless steel, aluminum, nickel, titanium, calcined carbon, or aluminum or stainless steel surface-treated with carbon, nickel, titanium, silver, etc. Specifically, transition metals that easily adsorb carbon, such as copper and nickel, can be used as the current collector. For example, the thickness of the negative electrode current collector can be 6 μm to 20 μm, but the thickness of the negative electrode current collector is not limited thereto.

[0114] The negative electrode active material may store or release lithium ions to generate electricity, and may include at least one of silicon-based active material particles and graphite-based active material particles.

[0115] The silicon-based active material particles can use one or more selected from the group consisting of Si, SiOx (0 < x ≦ 2), Si-C composite, and Si-Y alloy (Y is any one element selected from the group consisting of alkali metals, alkaline earth metals, transition metals, group 13 elements, group 14 elements, and rare earth elements).

[0116] The graphite-based active material particles can include one or more selected from the group consisting of artificial graphite, natural graphite, graphitized carbon fiber, and graphitized mesocarbon microbeads.

[0117] The content of the negative electrode active material can be 80 to 97% by weight based on the total solid content contained in the negative electrode active material layer.

[0118] The conductive material can improve the conductivity between the active material particles in the electrode or with the metal current collector and prevent the binder from acting as an insulator. The conductive material can be, for example, a mixture of one or more conductive materials selected from the group consisting of graphite, carbon black, carbon fiber, metal fiber, metal powder, conductive whisker, conductive metal oxide, activated carbon, and polyphenylene derivative. More specifically, it can be a mixture of one or more conductive materials selected from the group consisting of natural graphite, artificial graphite, super-p, acetylene black, ketjen black, channel black, furnace black, lamp black, summer black, denka black, aluminum powder, nickel powder, zinc oxide, potassium titanate, and titanium oxide.

[0119] The negative electrode binder can suppress separation between negative electrode active material particles or between the negative electrode and the current collector. As the negative electrode binder, a polymer commonly used in electrodes in the art can be used. Examples of such negative electrode binders include, but are not limited to, poly(vinylidene fluoride co-hexafluoropropylene), poly(vinylidene fluoride-co-trichloroethylene), poly(methylmethacrylate), poly(ethylhexylacrylate), poly(butylacrylate), poly(acrylonitrile), poly(vinylpyrrolidone), poly(vinylacetate), poly(ethylene-co-vinyl acetate), poly(ethylene oxide), polyarylate, cellulose acetate, and cellulose acetate butyrate. The cellulose acetate layer may include, but is not limited to, cellulose acetate propionate, cyano ethyl pullulan, cyano ethyl poly(vinylalcohol), cyanoethylcellulose, cyanoethylsucrose, pullulan, and carboxyl methyl cellulose.

[0120] positive electrode

[0121] The positive electrode according to the present invention may include a positive electrode current collector and a positive electrode active material layer disposed on at least one surface of the positive electrode current collector. The positive electrode active material layer may include a positive electrode active material, a conductive material, and a positive electrode binder.

[0122] For example, the positive electrode current collector is not particularly limited as long as it does not induce chemical changes in the battery and has high conductivity. Specifically, the positive electrode current collector may be made of copper, stainless steel, aluminum, nickel, titanium, baked carbon, copper or stainless steel surface-treated with carbon, nickel, titanium, silver, or the like, or an aluminum-cadmium alloy. The positive electrode current collector may usually have a thickness of 6 to 20 μm.

[0123] For example, the positive electrode active material may include a lithium transition metal oxide. The lithium transition metal oxide may be, for example, Li x1 CoO2(0.5 <x1<1.3)、Li x2 NiO2(0.5 <x2<1.3)、Li x3 MnO2(0.5 <x3<1.3)、Li x4 Mn2O4(0.5 <x4<1.3)、Li x5 (Ni a1 Co b1 Mn c1 )O2(0.5 <x5<1.3、0<a1<1、0<b1<1、0<c1<1、a1+b1+c1=1)、Li x6 Ni 1-y1 Co y1 O2(0.5 <x6<1.3、0<y1<1)、Li x7 Co 1-y2 Mn y2 O2(0.5 <x7<1.3、0≦y2<1)、Li x8 Ni 1-y3 Mn y3 O2(0.5 <x8<1.3、O≦y3<1)、Li x9 (Ni a2 Co b2 Mn c2 )O4(0.5 <x9<1.3、0<a2<2、0<b2<2、0<c2<2、a2+b2+c2=2)、Li x10 Mn2-z1 Ni z1 O4 (0.5 < x10 < 1.3, 0 < z1 < 2), Li x11 Mn 2-z2 Co z2 O4 (0.5 < x11 < 1.3, 0 < z2 < 2), Li x12 CoPO4 (0.5 < x12 < 1.3), and Li x13 It can be one or more selected from the group consisting of FePO4 (0.5 < x13 < 1.3).

[0124] The conductive material used for the positive electrode can be the same as or different from the conductive material used for the negative electrode.

[0125] The positive electrode binder can be the same as or different from the negative electrode binder.

[0126] electrolyte

[0127] The electrolytic solution according to the present invention can contain a solvent and a lithium salt.

[0128] Examples of the solvent according to the present invention include propylene carbonate (PC), ethylene carbonate (EC), diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), dimethyl sulfoxide, acetonitrile, dimethoxyethane, diethoxyethane, tetrahydrofuran, N-methyl-2-pyrrolidone, ethyl methyl carbonate (EMC), gamma-butyrolactone (GBL), and fluoroethylene carbonate (Fluoroethylene Carbonate). The alkyl group may be one or a mixture of two or more selected from the group consisting of FEC), methyl formate, ethyl formate, propyl formate, methyl acetate, ethyl acetate, propyl acetate, pentyl acetate, methyl propionate, ethyl propionate, ethyl propionate, and butyl propionate.

[0129] The lithium salt according to the present invention is, for example, NO3 - , F - , Cl - , Br - , I - , PF6 - The anions may include, for example,

[0130] The secondary battery according to the present invention may be a cylindrical, square, or pouch-shaped secondary battery, but is not particularly limited as long as it corresponds to a charge / discharge device.

[0131] According to yet another embodiment of the present invention, there is provided a battery module including the secondary battery as a unit cell, and a battery pack including the battery module. The battery pack can be used as a power source for at least one medium-sized or large-sized device selected from the group consisting of a power tool, an electric vehicle (EV), a hybrid electric vehicle (HEV), and an electric vehicle (PHEV), including a plug-in hybrid electric vehicle (PHEV), or a power storage system.

[0132] Hereinafter, the embodiments of the present invention will be described in detail so that a person having ordinary skill in the art to which the present invention pertains can easily implement the present invention. However, this is merely an example, and the scope of the present invention is not limited to the following content.

[0133] [Production Preparation Example 1: Production of Binder Slurry]

[0134] <Comparative Preparation Example 1: Preparation of binder slurry without surfactant>

[0135] A first particulate binder (average particle size D 50 500 nm) and a second particulate binder containing PVdF-HFP (content of HFP-derived units: 15 wt%) having a weight average molecular weight of 50,000 to 5,000,000 g / mol (average particle size D 50 150 nm) was added to a solvent (water) in a weight ratio of 5:5, and then stirred to prepare a binder slurry of Comparative Preparation Example 1 having a total solid content of 10 wt %.

[0136] <Comparative Preparation Example 2: Preparation of binder slurry containing surfactant in excess of the appropriate range>

[0137] A first particulate binder (average particle size D50 500 nm) and a second particulate binder containing PVdF-HFP (content of HFP-derived units: 15 wt%) having a weight average molecular weight of 50,000 to 5,000,000 g / mol (average particle size D 50 A binder slurry of Comparative Preparation Example 2 was prepared by adding a first particulate binder (150 nm) and a nonionic surfactant (perfluoroalkyltriethyleneoxide methyl ether in which the alkyl group has 6 carbon atoms) to a solvent (water) in a weight ratio of 5:5:0.5 (first particulate binder: second particulate binder: nonionic surfactant) and stirring the mixture to produce a binder slurry of Comparative Preparation Example 2 having a total solid content of 10 wt%.

[0138] <Preparation Example 1: Production of binder slurry containing appropriate amount of surfactant>

[0139] A binder slurry was prepared in the same manner as in Comparative Preparatory Example 2, but the weight ratio of the first particulate binder, second particulate binder, and nonionic surfactant (first particulate binder:second particulate binder:nonionic surfactant) was changed from 5:5:0.5 to 5:5:0.15, thereby producing the binder slurry of Implementation Preparatory Example 1, in which the total solids content was 10% by weight.

[0140] [Production Preparation Example 2: Production of composition for forming coating layer]

[0141] Polyvinylidene fluoride-hexafluoropropylene copolymer (Mw=350,000-500,000g / mol) with a hexafluoropropylene-derived unit content of 15% by weight was added to acetone (solvent) and dissolved at 60°C for 1 hour to prepare a polymer solution (solid content=25% by weight). 50After adding inorganic particles (Al2O3) having a particle size of 0.1 μm, the inorganic particles were crushed and pulverized in a ball mill for more than 12 hours to prepare a composition for forming a coating layer (total solid content: 30 wt%) in which polyvinylidene fluoride-hexafluoropropylene copolymer and Al2O3 were mixed in a weight ratio of 1:9.

[0142] [Manufacturing Preparation Example 3: Preparation of preliminary separation membrane (cross-section CCS)]

[0143] The composition for forming a coating layer according to Preparation Example 2 was coated on one side of a polyethylene porous substrate having a thickness of 5.0 μm and a porosity of 40% by a slot-die coating method, and then dried at 140° C. for 1 hour to form a coating layer having a thickness of 1.5 μm, thereby preparing a ceramic-coated separator (CCS) having a cross section corresponding to a preliminary separator.

[0144] [Experimental Example 1: Measurement of the contact angle of binder slurry to a porous substrate or coating layer]

[0145] The binder slurry (4 μL) according to Preparation Example 1 was dropped onto one side of the porous substrate or the coating layer, and the contact angle between the binder slurry and one side of the porous substrate or the coating layer was measured at room temperature using a contact angle measuring device (Attension Theta Flex, Biolin Scientific). The results are shown in Table 1 below.

[0146] [Experimental Example 2: Number of spots on one side of a porous substrate where the second binder slurry was not coated]

[0147] When the binder slurries according to Preparation Example 1 were coated on the surface of the porous substrate of the preliminary separator (CCS cross section), the number of spots that were not coated due to a decrease in wetting of the binder slurry was measured. Specifically, the number of spots with a diameter of 1 mm or more within a unit area of ​​10 cm x 10 cm was counted and shown in Table 1 below.

[0148] [Manufacturing Example 1: Manufacturing of secondary batteries]

[0149] <Comparative Example 1: Separation membrane in which the binder slurry of Comparative Preparation Example 1 is coated on both sides of the cross-sectional CCS>

[0150] The binder slurry of Comparative Preparation Example 1 was coated on both sides of the cross-sectional CCS of Preparation Example 3 by gravure coating, and then dried at 50° C. for 10 minutes to form a binder layer having a thickness of 0.5 μm on each side. As a result, the separator of Comparative Example 1 was finally manufactured.

[0151] <Comparative Example 2: Separation membrane in which the binder slurry of Comparative Preparation Example 2 is coated on both sides of the cross-sectional CCS>

[0152] A separation membrane was produced in the same manner as in Comparative Example 1, but the binder slurry of Comparative Preparation Example 2 was used instead of the binder slurry of Comparative Preparation Example 1.

[0153] <Example 1: Separation membrane with binder slurry of Preparation Example 1 coated on both sides of cross-section CCS>

[0154] A separation membrane was produced in the same manner as in Comparative Example 1, but the binder slurry of the Working Preparation Example 1 was used in place of the binder slurry of the Comparative Preparation Example 1.

[0155] [Experimental Example 3: Measurement of air permeability of cross-sectional CCS and separation membrane]

[0156] The air permeability measurement device used was an EG01-55-1MR model manufactured by Asahi Seiko Co., Ltd. Specifically, the preliminary separation membrane (CCS cross section), the separation membranes of Comparative Examples 1 and 2, and Example 1 were fixed to the hollow upper and lower tips of the air permeability measurement device, and the time it took for 100 cc of air to pass through was measured by applying a set pressure difference between the upper and lower tips to obtain the air permeability, and the results are shown in Table 1 below.

[0157] [Experimental Example 4: Resistance measurement of a cell equipped with a separator]

[0158] The separators of Comparative Examples 1 and 2, and Example 1 were interposed between SUS to manufacture respective coin cells. An electrolyte containing 1M LiPF6 and a mixture of ethylene carbonate and ethyl methyl carbonate in a volume ratio of 1:2 was injected into the coin cells. To measure the resistance of the coin cells, etc., resistance was measured through electrochemical impedance spectroscopy using VMP3 from BioLogic Science Instruments at 25°C, an amplitude of 10 mV, and a scan range of 0.1 Hz to 1 MHz, and the results are shown in Table 1 below. The resistance of the coin cells is preferably 1.0 Ω or less.

[0159] [Table 1]

[0160] Referring to Table 1, when ΔP(s / 100cc)=|Ps-Pc|<120 is satisfied and the first and second binder layers each contain a surfactant in an amount of more than 0 and less than 5.0 parts by weight per 100 parts by weight of the particulate binder, the wetting of the binder slurry is optimally controlled to prevent pores in the cross-sectional CCS (preliminary separator) and prevent an excessive increase in air permeability, thereby reducing the cell resistance.

[0161] In addition, by uniformly coating a binder slurry containing an optimal amount of surfactant on one side of a porous substrate or a coating layer, the thickness of the separator can be reduced to increase the energy density of the secondary battery. In addition, during the manufacture of an electrode assembly using heat and pressure, the adhesive strength to the electrode is increased, effectively preventing defects such as separator breakage.

[0162] Considering the above experimental results comprehensively, a new parameter was identified that can improve the coating ease of the binder slurry and reduce the cell resistance by satisfying ΔP(s / 100cc)=|Ps-Pc|<120 and including a surfactant in the binder layer. If ΔP(s / 100cc)=|Ps-Pc|<120 is not satisfied, the resistance of the cell having the separator may increase excessively even if the binder layer includes a surfactant and the binder slurry has excellent coating properties. If ΔP(s / 100cc)=|Ps-Pc|<120 is satisfied but the binder layer does not include a surfactant, the binder slurry has poor coating properties and the number of uncoated spots may increase excessively. In addition, by uniformly coating a binder slurry containing an optimal amount of surfactant on one side of a porous substrate or a coating layer, the thickness of the separator can be reduced to increase the energy density of the secondary battery. In addition, during the manufacture of an electrode assembly using heat and pressure, the adhesive strength to the electrode is increased, effectively preventing defects such as separator breakage.

[0163] Although the preferred embodiments of the present invention have been described in detail above, the scope of the present invention is not limited thereto, and various modifications and improvements made by those skilled in the art using the basic concept of the present invention defined in the following claims also fall within the scope of the present invention. [Explanation of symbols]

[0164] 100 Separation membrane for secondary batteries 10 Porous substrate 15 Spare separation membrane 20 Coating Layer 30a First binder layer 30b Second binder layer

Claims

1. A preliminary separation membrane including a porous substrate and a coating layer disposed on one surface of the porous substrate; a first binder layer disposed on one side of the coating layer; a second binder layer disposed on the other surface of the porous substrate; and Equipped with the first binder layer and the second binder layer each contain the same or different surfactants; A separator for a secondary battery that satisfies the following formula 1: [Formula 1] ΔP (s / 100cc) = |Ps-Pc|<120 In the formula 1, Ps is the air permeability of the separator for a secondary battery, and Pc is the air permeability of the preliminary separator.

2. The first binder layer and the second binder layer are 2. The separator for a secondary battery according to claim 1, wherein each of the separators comprises the same or different particulate binders.

3. The particulate binder is a first particulate binder, and 3. The separator for a secondary battery of claim 2, further comprising a second particulate binder that is the same as or different from the first particulate binder.

4. The first and second particulate binders each independently comprise: Polyacrylate (PA), polyacrylic acid (PAA), polyvinylidene fluoride (PVDF), polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-HFP), polybutyl acrylate (PBA), polystyrene (PS), polymethyl methacrylate (PMMA), polyethylene oxide (poly(ethylene 4. The separator for a secondary battery according to claim 3, comprising one compound, a copolymer of two or more compounds, or a mixture of two or more compounds selected from the group consisting of poly(ethylene oxide); poly(ethylene oxide) and poly(siloxane).

5. The surfactants may each independently be The separator for a secondary battery according to claim 2 , wherein the binder is contained in an amount of more than 0 and less than 5.0 parts by weight based on 100 parts by weight of the particulate binder.

6. The separator for a secondary battery according to claim 1 , wherein the surfactant comprises a non-ionic surfactant.

7. The nonionic surfactant is The separator for a secondary battery according to claim 6, which is one or more selected from the group consisting of perfluoroalkyltriethylene oxide methyl ether, polyoxyethylene alkyl ether, polyoxyethylene fatty acid ester, polyoxyethylene alkylphenol ether, sorbitan fatty acid ester, polyoxyethylene sorbitan fatty acid ester, sucrose fatty acid ester, polyfluorobutane sulfonate, and polyethylene oxide-polypropylene oxide copolymer, each of which has 6 carbon atoms in the alkyl group.

8. 2. The separator for a secondary battery according to claim 1, wherein the coating layer has a thickness of 0.1 to 10 μm.

9. 2. The separator for a secondary battery according to claim 1, wherein the first and second binder layers each have a thickness of 0.05 to 10 μm.

10. A method for producing the separator for a secondary battery according to claim 1, coating one side of the coating layer with a first binder slurry and then drying to form the first binder layer; coating the other surface of the porous substrate with a second binder slurry and then drying the second binder layer; A method for producing a separator for a secondary battery comprising the steps of:

11. The method for producing a separator for a secondary battery according to claim 10, which satisfies the following formula 2: [Formula 2] C A <50゜ In the above formula 2, C A is the contact angle of the first binder slurry with one surface of the coating layer at 25°C.

12. The method for producing a separator for a secondary battery according to claim 10, which satisfies the following formula 3: [Formula 3] C B <50゜ In the above formula 3, C B is the contact angle of the second binder slurry with the other surface of the porous substrate at 25° C.

13. A negative electrode; A positive electrode and The separator for a secondary battery according to claim 1 , interposed between the negative electrode and the positive electrode; An electrolyte; A secondary battery including:

Citation Information

Patent Citations

  • Composite separation membrane for electrochemical device including adhesive layer and electrochemical device provided with the same

    JP2018530860A

  • Separator for power storage device, winder using the same, lithium ion secondary battery, and power storage device

    JP2020170590A

  • Aqueous dispersion slurry for separator coating for power storage device and separator for power storage device using the same

    JP2020191179A

  • Separator for power storage device

    JP2022157163A

  • Method for manufacturing a separator for a secondary battery, separator manufactured by the method, and secondary battery including the separator

    JP2023525824A